2018
DOI: 10.1126/sciadv.aau8408
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoids manipulate a broad range of virus-host fusion via wrapping the HR2 domain prevalent in viral envelopes

Abstract: Natural triterpenoids, as virus-host fusion inhibitors, exhibit potential in expanding the current repertoire of antiviral agents.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 42 publications
(77 reference statements)
1
60
0
Order By: Relevance
“…The virus internalization assay was performed as previously described (Talarico et al, 2005;Si et al, 2018). BHK-21 cells confluent in six-well plates were infected with 500 pfu of viruses on ice.…”
Section: Assay For Virus Internalizationmentioning
confidence: 99%
“…The virus internalization assay was performed as previously described (Talarico et al, 2005;Si et al, 2018). BHK-21 cells confluent in six-well plates were infected with 500 pfu of viruses on ice.…”
Section: Assay For Virus Internalizationmentioning
confidence: 99%
“…It was reported that several types of triterpenoids can exhibit antiviral activities [81][82][83]. Earlier studies highlighted that UNA possesses antiviral potential as well.…”
Section: Antiviral Effectsmentioning
confidence: 99%
“…With respect to the physiological function of pentacyclic triterpenoids these compounds are considered as part of a defense system which defends plant against environmental stress, wound and injuries repair mechanism and enhanced the resistance against plant pathogens [12,13]. A variety of infectious organisms were reported inhibited by triterpenoids compounds, including fungi, viruses, bacteria, protozoa and parasites [14]. So, in these senses it has been shown as UA is an efficient antifungal against the infection of apple by Alternaria alternata that could be a useful alternative for this disease management [13].…”
Section: Sift Deskmentioning
confidence: 99%
“…So, in these senses it has been shown as UA is an efficient antifungal against the infection of apple by Alternaria alternata that could be a useful alternative for this disease management [13]. Also, OA and BA exert an inhibitory activity against influenza virus and hepatitis C virus infection binding to viral fusion proteins and disrupting viral entry into the host cells [14]. In root olive tree, pentacyclic triterpenes can be also part of a defense system that protects plant against different agents.…”
Section: Sift Deskmentioning
confidence: 99%
See 1 more Smart Citation